Building identity in the diaspora: (A) gastronomic discourse and the Arbëreshë in Calabria - Gallo, Giusy (E|C, 2020)
The question around the theme of the diaspora concerns the notion of identity: lost, rediscovered, constructed. One of the elements that contributes to build the identity of the diaspora is food as a communication system. The goal of this article is to show a core identity in the Arbëreshë of Calabria starting with the gastronomic discourse on shtrydhlat, a fresh pasta that is handmade in some communities. The preparation of shtrydhlat is expressed in a series of gestures that develop in the shape of the spiral, which also recurs in the vallja, a cultural performance. A working hypothesis concerns the narrative of the identity of the Arbëreshë diaspora and the organization of space in the spiral movement.